2021
DOI: 10.1111/hex.13186
|View full text |Cite
|
Sign up to set email alerts
|

Patient and public involvement cultures and the perceived impact in the vulnerable context of palliative care: A qualitative study

Abstract: Background Cultural values are crucial to the practice and impact of patient and public involvement (PPI) in research. Objective To understand different PPI cultures among research teams and the impacts of PPI associated with each culture type. Design A participatory action research design. Setting and participants The setting was 10 palliative care research projects. Seventeen patients and members of the public and 31 researchers participated. Intervention A programme consisting of four components: (1) traini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…Compensation is essential to recognizing patient research partner contributions to health research projects 38 . Similar to our findings, patient research partner relationships are known to flourish in a culture of trust 39 . Transparency is essential to trust and considered relational and social processes are essential in fostering effective engagement within research teams 16,18 .…”
Section: Discussionsupporting
confidence: 75%
“…Compensation is essential to recognizing patient research partner contributions to health research projects 38 . Similar to our findings, patient research partner relationships are known to flourish in a culture of trust 39 . Transparency is essential to trust and considered relational and social processes are essential in fostering effective engagement within research teams 16,18 .…”
Section: Discussionsupporting
confidence: 75%
“…Using authorship listing and information in the contribution and affiliation sections, 33 articles were identified as being co-authored by PRs. For one article we were unable to determine whether PRs had been co-authors, and thus classified this [ 51 ] as non-co-authored. Articles described inviting PRs with lived experience of the condition or service under investigation, yet in 5 articles the authors did not report any details on who the PRs were or reasons for selecting them [ 2 , 21 , 58 , 64 , 69 ].…”
Section: Resultsmentioning
confidence: 99%
“…Time The more steps the PRs are involved in, the more the influence of the PRs on the project and partnerships was reported as strong [ 9 , 39 , 51 , 53 ] suggesting a longitudinal causality. Time was also mentioned as a factor in shorter partnerships as time spent on informal talks pre- and post-meeting helped build the relationship [ 15 ] and allowed for time spent together to reflect during the process [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are growing efforts across the world to involve patients in clinical research and the dissemination of published results across all disciplines [39]. Melchior et al described a palliative care initiative in The Netherlands in which they trained patients and lay members of the public to prepare them for participation in research [40]. The investigators found that due to this training program, their project aims became more relevant to the intended audience.…”
Section: Patient Engagement In Melanoma Researchmentioning
confidence: 99%